'SIMLA' Educational Game-Based Learning Media for the Inculcation of Pancasila Symbols and Principles, Augmenting Independent Character - Diah Aulia Azizatur Rohmah; Sri Untari; Ade Eka Anggraini (Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
The transition from the K13 curriculum to an independent curriculum creates problems, especially in the learning process and learning media. A learning process needs to be supported by good learning media to achieve learning goals. This research aims to develop the educational game learning media "SIMLA" with material on the symbols and principles of Pancasila to strengthen the independent character of fourth-grade elementary school students. The type of research used is the research and development (R&D) ADDIE development model. The research subjects were material experts, media, teachers, and fourth-grade elementary school students. Data collection includes interview guides, validation instruments, and student questionnaires. This quantitative data was obtained from material, media, user/teacher, and student validator questionnaires. Qualitative data was obtained from suggestions and input from experts, users, and students. The validator analysis technique uses a Likert Scale. Data obtained from product trials and usage tests uses the Guttman scale. The results obtained from material validation were 87.5% (very valid), media validation 93.75% (very valid), user validation 100% (very valid), and product trials 100% (very practical/interesting). It is practical and fun to improve independent character. The results of the paired t-test show that this product is very effective in improving students' abilities. The educational game learning media produced using the Construct 3 application is valid and can improve student learning outcomes.